סמל שאינו מצליח לסמל: דימוי הקיבוץ ואופוזיציה כאפירמציה בדרך גבר ליגאל מוסינזון (1953) ובספרות "דור בארץ" בעשור הראשון למדינת ישראל - ליבמן ליאור (מכאן, 2024)
Yigal Mossinson’s 1953 novel The Way of a Man sparked controversy even before it was fully published. Ultimately forcing the writer to leave his home-kibbutz, Na’an, the critical-realist novel relates the loneliness of the individual and their suffocation within indifferent, insensitive surroundings, and the collapse of the family in the kibbutz. At a time of shattering changes brought about by the foundation of Israel which dramatically affected the kibbutz’s social fabric and its place in the nascent state, kibbutz critics and rank-members alike sharply condemned the novel. Accepting this view, later scholarship also considered it as hostile to the kibbutz. Contrary to the prevailing perception, this article suggests that Mossinson’s representation of the kibbutz in fact aims at repairing kibbutz society and rehabilitating its values within a disrupted context. Closely allied to aesthetic and political trends both within modern Hebrew literature and Marxist literary thought, the novel depicts the kibbutz-utopia by underscoring what is missing, staking out a ‘concrete-utopia’, by proceeding from the existing situation towards a better possible future. Moreover, the kibbutz ideal that emerges dialectically in the course of the novel through this emphasis on the negative meant to resist the state: Mossinson, like most of his canonical contemporaries, belonged to political circles which opposed the state in the name of the pre-state pioneering ethos. For them, the foundation of the state, rather than achieving fulfilment, produced a culturally traumatic rift in their self-understanding as realizing their own Zionist-socialist creed in their everyday life. Rejecting the state as a ‘final destination’, these writers sought to direct the state towards their political vision in their literary works. Regarded as the utmost embodiment of Zionist-socialist pioneering values, the kibbutz was a central image in their fictional world, shaped as a model and a symbol for Israel’s evolving society: the concrete realistic depiction of the kibbutz strove to reveal its unmediated affinity with the ideal of Jewish and universal-humanist salvation. These representations of the kibbutz, as exemplified in Mossinson’s novel, maintained its pre-state image, while ignoring the confrontation of the kibbutz with early statehood. Arguing that this representation reflected a reaction of shock resulting from the cultural trauma of the foundation of the state, this article traces how the kibbutz-symbol becomes an allegory: a sign in which a static essence is imposed on the dynamic reality and remains detached from it. And so, the absence of the kibbutz’s actual difficulties from the text, makes it politically irrelevant, unable to address reality – hence affirming what it resists. Focusing on the image of the kibbutz – which despite its centrality in the canonical literature of the period has not yet received separate scholarly attention – this article aims to offer a new historiographical perception of the corpus of the “1948 Generation.” Whereas it is usually understood in the dichotomous terms of either conformity with the hegemonic Zionist narrative, or individual critical expression – reading the “inside history” of the “48ers” literary works this analysis presents a dialectical approach, defining this body of texts as “affirmative opposition” or “oppositional affirmation”.